Atrichadenotecnum multispinosus sp. n. (Psocoptera: Psocidae) from southwestern China, with new synonyms and new combinations from Psocomesites and Clematostigma - Liu, Luxi; Yoshizawa, Kazunori; Li, Fasheng; Liu, Zhiqi (Zootaxa, 2013)
Atrichadenotecnum multispinosus sp. n. is described from southwestern China. Psocomesites and Clematostigma from China are discussed, with five species transferred to Atrichadenotecnum and four species placed as new synonyms. Keys to adult males and females of Atrichadenotecnum species are presented.